Case Report: Endovascular Treatment of Chronic Atherosclerotic Renal Artery Total Occlusions with Failed Medical Therapy - Li, Pengyu; Niu, Guochen; Yan, Ziguang; Zhang, Bihui; Yang, Min (Frontiers in Surgery, 2022)
Background Current guidelines generally no longer support revascularization for chronic renal artery occlusive diseases because results from randomized controlled trials favor medical therapy over angioplasty. However, increasing reports indicate that patients with renal artery occlusion (RAO) can benefit from revascularization under certain circumstances. Case summary Here, we present a patient with renal artery stenosis (RAS) who does not have refractory hypertension or fit any clinical trial inclusion criteria by far. Medical therapy failed to prevent the progression of RAS in this patient, leading to total occlusion of his right renal artery. This patient had progressive renal insufficiency but recovered renal function after endovascular treatment. Conclusion This case demonstrates that angioplasty can be beneficial in selected RAO patients, especially those with residual renal function and collateral perfusion.